Design of reinforced concrete structures subjected to external loads and restrained deformations - Faria, Rui (2019)
[Excerpt] The design of steel reinforcement in RC structures, under the combined effect of external forces and restrained shrinkage is a complex matter, which has been under discussion at an international level. The relevance of discussing the best practices, in this area of knowledge, is widely recognized in view of the insufficiencies in the regulatory framework applicable to the design of minimum reinforcement and cracking control for an adequate service life.[...]